Levator scapulae muscle asymmetry presenting as a palpable neck mass: CT evaluation. - Shpizner, B A; Holliday, R A (American Journal of Neuroradiology, 1993)
PURPOSE To define the normal CT anatomy of the levator scapulae muscle and to report on a series of five patients who presented with a palpable mass in the posterior triangle due to asymmetry of the levator scapulae muscles.PATIENTS AND METHODS The contrast-enhanced CT examinations of the neck in 25 patients without palpable masses were reviewed to establish the normal CT appearance of the levator scapulae muscle. We retrospectively reviewed the contrast-enhanced CT examinations of the neck in five patients who presented with a palpable mass secondary to asymmetric levator scapulae muscles.RESULTS In three patients who had undergone unilateral radical neck dissection, hypertrophy of the ipsilateral levator scapulae muscle was found. In one patient, the normal levator scapulae muscle produced a factitious "mass" due to atrophy of the contralateral levator scapulae muscle. One patient had an intramuscular neoplasm of the levator scapulae.CONCLUSION Asymmetry of the levator scapulae muscles, an unusual cause of a posterior triangle mass, can be diagnosed using CT.